Homero hecho ya español ou la traduction comme événement. Poèmes antiques et italiens en vers espagnols (1549-1556) - Aude Plagnard (Mélanges de la Casa de Velázquez)
Between 1549 and 1556, Spain saw an unprecedented spate of publications of verse translations of classical and Italian epic poems. This chronological coincidence is symptomatic of a renewed interest in epic poetry, which prefigured the flourishing of the genre in the Iberian Peninsula in the second half of the century. We suggest that this accumulation should be viewed as a literary event and those texts should be read as the first epic poems in Spanish. More faithful to the original texts and set in an Italianate verse form, these translations marked a departure from earlier efforts and spread a new image of those works. In this way, poets lent their pens to the enrichment of the Spanish literary and linguistic heritage. Contemporaries read these works as original poems, and they tended to he published as such.